„Lekarzu, ulecz samego siebie!” Etyka stosowana wobec przemian społecznych, słabości metodologicznych oraz wyzwań instytucjonalnych - Rotengruber, Przemysław (Humaniora. Czasopismo Internetowe, 2025)
The role of the humanities and social sciences is to seek answers to questions that concern us as individuals and as participants in collective life. We want to know how the social world is organized – what laws govern it and what is changing in it. In the case of applied ethics, other tasks are added to this. We expect it not only to justify claims to the validity of moral judgments concerning its social environment, but also to prove its effectiveness in solving problems of the academic world. This is a matter of (its) credibility. It is difficult to blame people seeking agreement for being distrustful of knowledge that did not help its creators. The aim of this article is to discuss both issues – to determine what methodological difficulties representatives of (different branches of) applied ethics struggle with and what serious organizational challenges they must face.